Petrografia e geoquímica dos ortoanfibolitos das unidades Novo Gosto e Gentileza, Domínio Canindé, Faixa de Dobramentos Sergipana, NE-Brasil - Liz, Leidiane Cerqueira de Carvalho de (2017)
In the Canindé Domain, Northern portion of Sergipano Fold Belt, NE-Brazil, occur an association of metamorfized mafic igneous rocks from the Novo Gosto and Gentileza units.Those rocks represent important pieces in the Sergipano Fold Belt geological evolution. The Canindé Domain has been scenario of several interpretations about the tectonic and petrogenetic settings, due to intense deformation and metamorphism that obliterated much of the Canindé Domain rocks original features. Petrographic and geochemical data from the ortho-amphibolites of the Novo Gosto and Gentileza units showed this work contribute to discuss the igneous processes involved in the protoliths genesis, therefore building up to the Canindé Domain tectonic model definition and the major evolutionary aspects. The petrographic data indicate that the studied rocks show Amphibolite Facies paragenesis, marked by hornblende and plagioclase, with retrometamorphic transformations to Greenschist Facies, defined by biotite, epidote, chlorite and sericite paragenesis. These transformations, which were more intense in areas with shear zones concentrations, are probably, the result of hydrothermal fluid action. In spite of the superimposed metamorphic processes, it was possible to observe igneous relicts features, such as blast-glomeroporphiritic, blast- intergranular and blast-subophytic textures. The chemical data suggest that the protoliths of the studied rocks of the Novo Gosto and Gentileza units correspond to basalts with tholeiitic affinity. These basalts are divided into high-Ti (> 2 % TiO 2 ) and low-Ti (< 1,19 % TiO 2 ). Gentileza Unit rocks correspond to andesites and basaltic andesites with tholeiitic to calc- alkaline affinity. The geochemical data interpretation suggest that the igneous protoliths of the studied rocks of the Novo Gosto and Gentileza units were formed in a continental rift environment, derived from magmas generated in different proportions of mixtures between enriched and depleted reservoirs, with OIB-type components contribution. Ratios and correlations among incompatible elements indicate crustal contamination participation in the igneous protoliths generation of both units.